Representation of Character Education Values in the Film Home Sweet Loan and Its Implications for Indonesian Language Learning - Anzahra, Anzalika; -, Fauziyah; Fazillah, Nur; Zuyyina, Rifni; Diana, Rahma; Nabila, Putri; Sundana, Lina (Jurnal Bahasa Indonesia Prima (BIP), 2025)
This study aims to examine the representation of character education values in the film Home Sweet Loan and its implications for teaching Indonesian language in secondary schools. As a form of modern literature, film has the potential not only to serve as entertainment but also as an educational medium that conveys moral messages and life values. This research employs a descriptive qualitative method with data collected through observation and note-taking of scenes, dialogues, and character interactions in the film. The collected data were then analyzed through the stages of reduction, classification based on categories of character values, interpretation of dialogue context, and conclusion drawing to identify dominant value patterns. The findings reveal 11 data excerpts that represent five main character education values, namely responsibility, honesty, self-awareness, justice, and family communication. These values are reflected through the dialogues and actions of the main character, particularly in facing economic pressures, patriarchal cultural dominance, and adolescent identity crises. The results indicate that Home Sweet Loan is not only relevant as a reflection of the social reality of today’s youth but also effective as a teaching medium in Indonesian language learning that integrates cognitive, affective, and moral aspects of students. This study is expected to enrich the literature on character education through a contextual, film-based approach and provide alternative learning media that are engaging and meaningful for students.